Assessment of efficacy of locking compression plate in distal femur fractures - A. A., Faizal Ali; Karunakaran, Govind; Hameed, Hijas (International Surgery Journal, 2021)
Background: Distal femur fractures account for an estimated 6% of all femur fractures. Our study aims at evaluating the functional and radiological outcome in distal femur fractures treated with locking compression plate (DF-LCP). Methods: Patients undergoing LCP were assessed postoperatively both functionally and radiologically. Oxford Knee Score was used to assess the functional outcome. With a maximum score of 48, a score of more than 41 is scaled as excellent, 34 to 40 as good functional status, 27 to 33 as fair and score less than 27 as poor functional result. Results: Extra-articular fractures were the commonest (66.7%) type of fractures [simple-6.7%; metaphyseal wedge-20%; metaphyseal complex-40%] followed by complete articular fractures (26.7%) [Simple articular metaphyseal comminution-16.7%; metaphyseal and intra-articular comminution-10%] and partial articular fractures (6.7%) [Medial condyle-3.3%; coronal plane-3.3%]. Most of them had right sided femur injury (66.7%) and had history of fall (70%). Radiologically, 90% exhibited no complications and had united appropriately. Functionally the mean oxford knee score was 41.53±1.69 which ranged from a score of 38 to a maximum of 44. Highest proportion i.e., 63.3% had excellent outcome followed by good functional outcome and none showed fair or poor outcomes. Conclusions: LCP has shown very good radiological and functional outcomes with hundred percent union of the distal femur fractures. Hence it can be used successfully in distal femur fractures.